Development of a Message-Oriented Middleware for a Heterogeneous Distributed Database Systems - Khalid, Lamia H; Younis, Manal F (Al-Nahrain Journal of Science, 2013)
Abstract:Middlewares are enabling technologies for the development, deployment, execution and interaction of applications. These software layers are standing between the operating systems and applications. They have evolved from simple beginnings hiding network details from applications into sophisticated systems that handle much important functionality for distributed applications providing support for distribution, heterogeneity and mobility.This paper concerns with the development of a Message_Oreinted Middleware (MOM) for a distributed database system. Middleware is a distributed software layer, or ‘platform’ which abstracts over the complexity and heterogeneity of the underlying distributed environment with its multitude of network technologies, machine architectures, operating systems and programming languages. The role of this middleware is to ease the task of designing, programming and managing distributed database applications by providing a simple, consistent and integrated distributed programming environment. It provides integrity and security to these databases.